Analisis Rentabilitas Ekonomi Agroindustri Pupuk Organik Cair di Desa Cicalengka Wetan - Hardiyanto, Tito (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
Agroindustry is a combination of the words agriculture and industry, referring to businesses/industries that primarily use agricultural raw materials. Additionally, agroindustry can also mean industries that produce products for agricultural production (agricultural inputs). One example of agroindustry for agricultural inputs is the liquid organic fertilizer agroindustry. The existence of liquid organic fertilizer agroindustry is generally run by the community, either individually or in groups, thus requiring an economic profitability study to determine the ability to generate profits from the capital invested in that agroindustry. The issues examined in this study include the total cost value, total revenue, income, and profitability of the liquid organic fertilizer agroindustry in a single production process in Cicalengka Wetan Village, Cicalengka District, Bandung Regency. The sampling technique was conducted through purposive sampling at the Bangbara Sadulur Makmur Cooperative. The data analysis was conducted descriptively and quantitatively. The research results indicate that the production output of the liquid organic fertilizer agroindustry in one production process reaches 5,000 liters, with a selling price of Rp. 75,000 per liter. The total revenue obtained is Rp. 375,000,000, and the income earned is Rp. 7,726,707.86. The profitability value of the liquid organic fertilizer agroindustry in Cicalengka Wetan Village in one production process is 2.10 percent, meaning that the ability of the liquid organic fertilizer agroindustry to generate profit is 2.10 percent of the capital invested in one production process